Simultaneously dominating all spanning trees of a graph - Sebastian Johann; Sven O. Krumke; Manuel Streicher (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
We investigate the problem of simultaneously dominating all spanning trees of a given graph. We prove that on 2-connected graphs, a subset of the vertices dominates all spanning trees of the graph if and only if it is a vertex cover. Using this fact we present an exact algorithm that finds a simultaneous dominating set of minimum size using an oracle for finding a minimum vertex cover. The algorithm can be implemented to run in polynomial time on several graph classes, such as bipartite or chordal graphs. We prove that there is no polynomial time algorithm that finds a minimum simultaneous dominating set on perfect graphs unless P=NP. Finally, we provide a 2-approximation algorithm for finding a minimum simultaneous dominating set.